Energy Saving and Climate Adaptation of Buildings: A Paradox?. (June 2019) - Golz, S; Nikolowski, J; Naumann, T
Abstract: The European climate policy goals include (a) reducing energy consumption and avoiding the emission of climate-affecting gases as well as (b) adapting to existing and expected climate change. The synergetic implementation of both goals forms a central challenge particularly for the building stock. There is evidence that damage to buildings due to extreme weather events (e.g. heavy rain, fluvial flooding, hail, summer heat) steadily increase. Therefore, several national strategies and action plans in European member states formulate requirements for climate-adapted modernisation and retrofitting of existing residential buildings. The paper explores the conflicts between the two named goals at the building level, since building energy saving measures are unfortunately not in any case consistent with the goal of increased climate adaptation, as they undesirably increase the vulnerability of buildings. For this purpose, the paper first deals with the structural design of selected building types, which have been refurbished in order to optimize their energy efficiency. Second, it analyses and evaluates the physical vulnerability of existing buildings against extreme weather events. Then, the paper proposes some practical options on how to achieve the two goals effectively. Finally, some implications for future research and practice are discussed.